HOW TO MAKE PEOPLE COMMITED TO ORGANIZATIONAL CHANGE: READINESS OR EMPOWERMENT? - Nabilla Qolby; Wustari L. Mangundjaya (Sean Institute, 2023)
Change is inevitable and imperative, hence affective commitment to change for employees is necessary when the organization makes a change. The aim of this study is to examine whether individual readiness for change or psychological empowerment can be the predictors of affective commitment to change. The study involving 315 banking employees in Jakarta used correlational design. The data were collected using Affective Commitment to Change, Individual Readiness for Change, and Psychological Empowerment Questionnaire. Data were analyzed using statistical regression techniques to observe the influence of predictor variables on the outcome variable. Results revealed that individual readiness for change and psychological empowerment and had significant positive relationship on predicting affective commitment to change. This study also showed that individual readiness for change is the stronger predictor of affective commitment for change compared to psychological empowerment. This study will be beneficial to the management and change leader in preparing the success of organizational change by developing people to be ready for organizational change.